COVID-19 as a Catalyst of Food Security Crisis. Whether the Existing System of Agriculture Can Remain the Same - Oleksandra Ovchynnykova (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego, 2022)
From 2019 to 2022, since the outbreak of the COVID-19 pandemic, the global percentage of hunger rose by 150 million people, which is 10% of the world population. At the same time, one-third of food is thrown away because it cannot reach the final consumer. Climate change, natural catastrophes, wars leading to humanitarian crises are the main and ongoing causes of hunger. COVID-19 acted as an accelerator of processes that exacerbate the food security crisis, to which import-dependent countries are especially sensitive. Quarantine that was introduced as a tool to combat the spread of the COVID-19 acted as a catalyst of social, economic, political, ecological, and food crisis that is displayed in the global economic system and in agriculture – its subsystem. At first glance, the increase in the percentage of starving populations on the planet is explained by poverty and the inability to purchase basic food products; a rise in prices was caused by breaks in logistics chains, the increase in the price of energy carriers, and economic shifts caused by the lockdown. In practice, despite the constantly growing volumes of global production of agro-industrial products, the balance between demand and supply of products that ensure the world's food security has been disturbed. The research problem lies in the insufficient determination of intangible causes of hunger, other than those caused by poverty and social inequality. The aim of the research is to show the prospects of the aggravation the food security crisis due to excess of food demand over supply, and to propose theoretical ways out of the crisis. The quantitative method of panel data research was used to prepare the article. The visualization method was used to simplify the perception of the proposed array of information. It is possible to overcome such social problems as hunger, poverty, climate and ecology problems caused by the increase in the temperature on the planet's surface, ocean pollution, and soil degradation only through adaptation and achieving synergy between the planet’s ecosystems. Agriculture as a main factor of food security should be transformed through implementing principles of climate-optimized agriculture and blue economy (use of ocean resources) as a source of “blue food” to achieve food sustainability.